2020
DOI: 10.1186/s12916-019-1489-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tuberculosis screening and retention interventions on early antiretroviral therapy mortality in Botswana: a stepped-wedge cluster randomized trial

Abstract: Background: Undiagnosed tuberculosis (TB) remains the most common cause of HIV-related mortality. Xpert MTB/ RIF (Xpert) is being rolled out globally to improve TB diagnostic capacity. However, previous Xpert impact trials have reported that health system weaknesses blunted impact of this improved diagnostic tool. During phased Xpert rollout in Botswana, we evaluated the impact of a package of interventions comprising (1) additional support for intensified TB case finding (ICF), (2) active tracing for patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…Strengths of this study include the use of data from prospective cohorts nested within clinical trials, meaning there was minimal missing covariate data and strong ascertainment of the primary outcome of interest (6-month ART mortality) (e.g., only one patient was LTFU from the XPRES cohort and was excluded from this analysis [ 16 ]). Additional strengths include the relatively high screening accuracy in both the XPRES and TBFT cohorts, from two geographically separate cohorts, with very different cohort characteristics (e.g., XPRES enrollees represent general outpatient ART enrollees while TBFT enrollees had homogenously low CD4 counts (< 150/μL)).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Strengths of this study include the use of data from prospective cohorts nested within clinical trials, meaning there was minimal missing covariate data and strong ascertainment of the primary outcome of interest (6-month ART mortality) (e.g., only one patient was LTFU from the XPRES cohort and was excluded from this analysis [ 16 ]). Additional strengths include the relatively high screening accuracy in both the XPRES and TBFT cohorts, from two geographically separate cohorts, with very different cohort characteristics (e.g., XPRES enrollees represent general outpatient ART enrollees while TBFT enrollees had homogenously low CD4 counts (< 150/μL)).…”
Section: Discussionmentioning
confidence: 99%
“…In the second phase, the Xpert® MTB/RIF assay (Cepheid; Sunnyvale, CA) (Xpert) was initiated in place of sputum smear microscopy for TB diagnosis. Details of these interventions have been previously published [ 16 ] and are provided in a supplementary appendix (see Additional file 2 , text describing enrollment and enhanced care interventions). We have previously shown that there was no significant difference in 6-month ART mortality between the two prospective phases of XPRES [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations